Serum metabolites as early detection markers of non-muscle invasive bladder cancer in Chinese patients - Zhao, Yi; Sun, Wei; Ji, Zhigang; Liu, Xiaoyan; Qiao, Yi (Frontiers in Oncology, 2023)
Background: Biomarkers of different stages and grades of bladder cancer (BC) are important in clinical work. The objective of our study was to investigate new biomarkers of early-stage BC with liquid chromatography-high resolution mass spectrometry (LC-HRMS) using serum samples. Methods: A total of 215 cases were included in our study, including 109 healthy adults as the control group and 106 non-muscle invasive bladder cancer (NMIBC) patients as the Bca group. Serum samples were collected from BC patients in the early stage, called NMIBC, and healthy people before surgery. We used LC-HRMS to distinguish NMIBC patients from controls and distinguish low-grade NMIBC patients from controls. Results: An apparent difference between the NMIBC group and the control group was visualized by unsupervised principle component analysis (PCA). Metabolite panels for 16-hydroxy-10-oxohexadecanoic acid, PGF2a ethanolamide, sulfoglycolithocholate and threoninyl-alanine were used to distinguish the two groups. The area under curve (AUC) of the panels was 0.985, and the sensitivity and specificity were 98.63% and 98.59%, respectively. To distinguish low-grade NMIBC patients from healthy controls, serum metabolic profiling differences between the control group and low-grade NMIBC samples were also analysed. Metabolite panels of L-octanoylcarnitine, PGF2a ethanolamide, and threoninyl-alanine showed good discrimination performance. The AUC of the panels was 0.999, and the sensitivity and specificity were 97.8% and 100%, respectively. Conclusion: Metabolomics analysis of serum samples can distinguish NMIBC from controls, particularly early-stage low-grade NMIBC.